A study of socioeconomic impacts on local businesses along Jalan Hang Tuah with the existence of UiTM Kampus Bandaraya Melaka / Nur Kholilah Kamarozzaman and Nuzul Ferhanis Ahmad Fadzil - Kamarozzaman, Nur Kholilah; Ahmad Fadzil, Nuzul Ferhanis (Faculty of Administrative Science and Policy Studies, 2012)
UiTM Kampus Bandaraya Melaka is one of the educational institutions that located at Jalan Hang Tuah, Melaka. With its existence it may give positive socioeconomic impacts (in general) specifically in term of life prospects on the local businesses established located surrounding the UiTM Kampus Bandaraya Melaka. The local businesses usually can be maintained with stability of financial condition, the price offered, continuous demands from people and ability to fulfill the customer’s demands and preferences. To ensure the increases of profitability as well as the expansion of business which the location factors; near to the university become one of the key strategies to successfully develop the business for long-lasting. The purpose of this study was to examine the factors contributing towards life prospects on local businesses at Jalan Hang Tuah with the existence of UiTM Kampus Bandaraya Melaka. The factors relates to this study are students’ expenditure, employment offered and business opportunity.